On no man’s land: Subjective experiences during unresponsive and responsive sedative states induced by four different anesthetic agents - Radek Linda; Koskinen Lauri; Sandman Nils; Laaksonen Lauri; Kallionpää Roosa E.; Scheinin Annalotta; Rajala Ville; Maksimow Anu; Laitio Timo; Revonsuo Antti; Scheinin Harry; Valli Katja (Elsevier, 2022)
To understand how anesthetics with different molecular mechanisms affect consciousness, we explored subjective experiences recalled after responsive and unresponsive sedation induced with equisedative doses of dexmedetomidine, propofol, sevoflurane, and S-ketamine in healthy male participants (N = 140). The anesthetics were administered in experimental setting using target-controlled infusion or vapouriser for one hour. Interviews conducted after anesthetic administration revealed that 46.9% (n = 46) of arousable participants (n = 98) reported experiences, most frequently dreaming or memory incorporation of the setting. Participants receiving dexmedetomidine reported experiences most often while S-ketamine induced the most multimodal experiences. Responsiveness at the end of anesthetic administration did not affect the prevalence or content of reported experiences. These results demonstrate that subjective experiences during responsive and unresponsive sedation are common and anesthetic agents with different molecular mechanisms of action may have different effects on the prevalence and complexity of the experiences, albeit in the present sample the differences between drugs were minute.